The Influence of HR Analytics on Managerial Decision-Making in Talent Management in the Digital Era at Pt. Saitama Stamping Indonesia - Sheva Prasetyo Budi Rahayu; Uus Mohammad Darul Fadli; Ery Rosmawati (Research in Management of Technology and Business, 2025)
This study aims to analyze the influence of HR Analytics on managerial decision-making in the context of talent management in the digital era at PT Saitama Stamping Indonesia. The method used is quantitative with a survey of 64 respondents, consisting of company employee position holders. Data was collected through an online questionnaire and then analyzed using SmartPLS4. The results showed that HR Analytics significantly influenced managerial decision-making. Key dimensions such as data collection, predictive analytics, efficiency, and skill gap analysis play an important role in data-driven talent management. In addition, the results also reveal that implementing HR Analytics helps improve the effectiveness of talent management strategies through alignment of organizational goals, employee development, and retention management. The implication of this research is the need for companies to prioritize the adoption of analytics technology in human resource management to increase competitiveness in the digital era. This research contributes to the literature by filling the gap in adopting HR Analytics in the Indonesian manufacturing sector, particularly in human resource management.